A Diastereoselective Catalytic Approach to Pentasubstituted Pyrrolidines by Tandem Anionic‐Radical Cross‐Over Reactions. Issue 3 (7th December 2021) - Hidasová, Denisa; Pohl, Radek; Císařová, Ivana; Jahn, Ullrich
Abstract: Pentasubstituted pyrrolidines are ubiquitous constituents of natural products and drugs, however the access options to them especially with respect to absolute and relative stereochemistry are not well developed. We report an asymmetric synthesis of N, 2, 3, 4, 5‐pentasubstituted pyrrolidines by oxidative single‐electron transfer‐catalyzed tandem aza‐Michael addition/radical 5‐exo cyclization/oxygenation reactions. The absolute stereochemistry is set by applying readily accessible chiral allylamines in asymmetric conjugate additions to various β‐substituted‐α, β‐unsaturated esters, which dependent on the substituent R 2 sets the configuration of the two stereocenters next to the amine function, whereas two more are diastereoselectively generated by the radical 5‐exo cyclization step. This allows the diastereodivergent single‐step synthesis of pyrrolidines with four contiguous stereogenic centers. The stereoselectivity is rationalized by a predictive model. Abstract :